A Review of the Some Fixed Point Theorems for Different Kinds of Maps - Kalaf, Bayda Atiya; Hussein Maibed, Zena (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The focus of this article, reviewed a generalized  of contraction mapping and nonexpansive maps and recall some theorems about the existence and uniqueness of common fixed point and coincidence fixed-point for such maps under some conditions. Moreover, some schemes of different types as one-step schemes ,two-step schemes and three step schemes (Mann scheme algorithm, Ishukawa scheme algorithm, noor scheme algorithm, .scheme algorithm,  scheme algorithm Modified  scheme algorithm arahan scheme algorithm and others. The convergence of these schemes has been studied .On the other hands, We also reviewed the convergence, valence and stability theories of different types of near-plots in convex metric space.